Surgical approach of rectal prolapse in feline: Case report - Viliotti, Tatianne; Lima, Anne Nelizia Holanda de; Rodrigues, Ingrid Rabelo; Feitosa, Aline Silveira; Ferraz, Richard Elaino de Oliveira; Santos, Rebeca de Melo; Ceni, Sarah Ary; Fernandes, Maria Ester Crispim Nogueira (Pubvet, 2018)
Rectal prolapse is a protrusion or eversion of the rectal mucosa from the anus and it is more reported in young animals. It is usually a consequence of underlying disorders intestinal diseases that cause diarrhoea and. The present study reports a case of rectal prolapsed in a cat puppy associated to necrose of the rectum, disquesia and emaciation. A feline S.R.D, 2 months old, was attended at the Metropolitan Veterinary Hospital, Caucaia, Ceará, Brazil, presenting the prolapsed rectum, tenesmus, dyskinesia, anorexia, emaciation, prostration and regions of necrosis in the prolapsed rectum. Haematological and biochemical tests revealed anemia and ALT increases. The surgical treatment consisted resection of restum and it was made an anastomose throue in the application of cross anchors and resection of the prolapsed mass and in the application of separate single sutures to make the anastomosis. The patient was reassessed in the following weeks and showed a return to the normal physiological functions of defecation. It is concluded that rectal amputation may be an alternative for the surgical treatment of rectal prolapse in felines.